모션타이포그래피의 움직임을 통한 감성전달 - 손민정(Min Jeong, Son); 이현주(Hyun Ju, Lee) (디지털콘텐츠학회논문지, 2011)
모션타이포그래피는 디지털사회가 요구하는 감성적인 커뮤니케이션에 효과적인 수단으로 활용될 수 있는 요체가 된다. 이에 따라 본 연구에서는 모션타이포그래피로 감성을 표현하기 위하여 움직임의 특성을 연구하는 것을 목적으로 사용자 감성평가를 통해 모션타이포그래피의 감성척도를 구성하고 움직임에 대한 이미지 분포를 파악하였다. 본 연구는 문헌연구와 실험조사를 통하여 감성어휘를 수집하였고 KJ법과 클러스터 분석법으로 대표어휘를 추출하였다. 연구 결과, ‘차분한-활동적인’, ‘부드러운-딱딱한’ 축으로 구성된 모션타이포그래피 감성척도 공간을 구성하였으며, 모션타이포그래피의 움직임은 사용자에게 특정한 감성반응을 유발한다는 것을 알 수 있었다. 향후에 본 논문의 결과와 함께 감성어휘별 시각요소의 특성을 도출한다면 일반인도 비교적 손쉽게 모션타이포그래피를 제작할 수 있는 가이드라인이 제시될 수 있을 것이다. MotionTypography is crucial to effective emotional communication in digital society. In this paper, I study movements to represent emotion using motiontypography and approach two goals: First to define an emotional measure by means of emotion assesses by the public, Second to research image characteristics corresponding to movements. In this dissertation, we collect emotional words by literature and experimental surveys and extract representative emotional words using KJ method and clustering analysis. The results of research, the emotional axes selected for motiontypography represent ‘calm to active’ and ‘soft to stiff', the viewers feel a specific emotional state from some movements of motiontypography. If, we investigate the relationship of motiontypographic visual elements with emotional words are achieved together, I think it will serve as a motiontypographic guideline that enables helping the public to easily produce motiontypography. KCI Citation Count: 4